New Horizons in Systemic Practice with Children and Families - Myra, Siv Merete; Grøver, Tone; Axberg, Ulf (Palgrave Texts in Counselling and Psychotherapy,, 2024)
This open access book illustrates how systemic theory, as both a meta-theory and a relational organic theory, can be a suitable framework for understanding and appreciating the new horizons of systemic practice with children and families in their various contexts. The different chapters shed light on how systemic perspectives, as they are presented in their varying contexts, promote hope by giving room for reflections on uncertainty, change, opportunities, interconnections, and differences. The authors describe and reflect on how systemic approaches can be useful for practitioners and make space for a multiplicity of different perspectives that address the needs of children and those assisting them in their various settings, where children grow and develop in the context of their unique needs and challenges. It covers safeguarding children's rights through parental separation and divorce; families experiencing anticipatory grief; parents struggling with substance use problems; gender incongruence; eating disorders; systemic perspectives on psychiatric diagnosis; children with disabilities; and systemic practice in school. The book will be a source of inspiration, as the purpose is to illustrate the systemic field in constant motion, which encourages, maybe even requires a plurality of theories, perspectives and approaches. But, most importantly, it demonstrates how working with children and families is a privilege. Siv Merete Myra is an experienced systemic therapist and Associate Professor in Family Therapy and Systemic Practice at VID Specialized University, Norway. Tone Grøver is an experienced systemic therapist and Associate Professor in Family Therapy and Systemic Practice at VID Specialized University, Norway. Ulf Axberg is an experienced systemic therapist and Professor in Family Therapy and Systemic Practice at the VID Specialized University, Norway.